The International Crash of October 1987: Causality Tests - Malliaris, A. G.; Urrutia, Jorge L. (Journal of Financial and Quantitative Analysis, 1992)
The paper analyzes lead-lag relationships for six major stock market indexes: New York S&P 500, Tokyo Nikkei, London FT–30, Hong Kong Hang Seng, Singapore Straits Times, and Australia All Ordinaries, for time periods before, during, and after the October 1987 market crash. Unidirectional and bidirectional causality tests are conducted by means of the Granger methodology. Practically no lead-lag relationships are found for the pre-crash and post-crash periods. However, important feedback relationships and unidirectional causality are detected for the month of the crash. There is also an increase in contemporaneous causality during and after the month of the crash. In general, our findings suggest that the October 1987 market crash probably was an international crisis of the equity markets and that it might have begun simultaneously in all the national stock markets.